Immersive 3D Virtual Reality Cancellation Task for Visual Neglect Assessment: A Pilot Study - Knobel, Samuel E. J.; Kaufmann, Brigitte C.; Gerber, Stephan M.; Cazzoli, Dario; Müri, René M.; Nyffeler, Thomas; Nef, Tobias (Frontiers in Human Neuroscience, 2020)
Background: Unilateral spatial neglect is an attention disorder frequently occurring after a right-hemispheric stroke. Neglect results in a reduction in quality of life and performance in activities of daily living. With current technical improvements in virtual reality technology, training with stereoscopic head-mounted displays has become a promising new approach for the assessment and the rehabilitation of neglect. The focus of this pilot study was to develop and evaluate a simple visual search task in virtual reality for head-mounted displays. The virtual reality system was tested regarding feasibility, acceptance, and potential adverse effects in healthy controls and right-hemispheric stroke patients with and without neglect. Methods: The virtual reality system consisted of two main components, a head-mounted display to present the virtual environment, and a hand-held controller for the interaction with the latter. The task followed the rationale of diagnostic paper-pencil cancellation tasks; i.e. the participants were asked to search targets among distractors. However, instead of a two-dimensional setup, the targets and distractors were arranged in three dimensions, in a sphere around the subject inside its field of view. Usability and acceptance of the task, as well as the performance in the latter, were tested in 15 right-hemispheric subacute stroke patients (10 of whom with and five of whom without unilateral spatial neglect) (mean age: 67.1 ±10.5 years) and 35 age-matched healthy controls. Results: System usability and acceptance were rated as high both in stroke patients and healthy controls, close to the maximum score of the questionnaire scale. No relevant adverse effects occurred. There was a high correlation (r= 0.854, p= 0.002) between the Center of Cancellation (an objective neglect measure) calculated from a paper-pencil cancellation task (Sensitive Neglect Test) and the newly developed virtual reality cancellation task. Conclusion: Overall, the developed visual search task in the tested virtual reality system is feasible, well-accepted, enjoyable and does not evoke any significant negative effects, both for healthy controls and for stroke patients. Findings with respect to task performance show that the ability of the virtual reality cancellation to detect neglect in stroke patients is similar to paper-pencil cancellation tasks.